Non-operative management of a splenic laceration in a patient with the Proteus syndrome. Issue 2 (March 1997) - Ceelen, W; De Waele, J; Kunnen, M; de Hemptinne, B
Abstract : An adult patient with the Proteus syndrome sustained a grade III splenic laceration after falling off a horse. Clinical features of this rare disorder include subcutaneous and visceral hamartomatous tumours. The patient also suffered from chronic intravascular coagulation associated with extensive haemangiomatosis (Kasabach-Merritt syndrome). Considering the visceral anomalies and abnormal coagulation, a non-operative approach was preferred despite considerable transfusion requirement, and the patient successfully underwent embolisation of the splenic artery. This is the first reported case of splenic injury in a patient with Proteus syndrome.